Modulating the activity of short arginine-tryptophan containing antibacterial peptides with N-terminal metallocenoyl groups - Albada, H. Bauke; Chiriac, Alina-Iulia; Wenzel, Michaela; Penkova, Maya; Bandow, Julia E.; Sahl, Hans-Georg; Metzler-Nolte, Nils (Beilstein Journal of Organic Chemistry, 2012)
A series of small synthetic arginine and tryptophan containing peptides was prepared and analyzed for their antibacterial activity. The effect of N-terminal substitution with metallocenoyl groups such as ferrocene (FcCO) and ruthenocene (RcCO) was investigated. Antibacterial activity in different media, growth inhibition, and killing kinetics of the most active peptides were determined. The toxicity of selected derivatives was determined against erythrocytes and three human cancer cell lines. It was shown that the replacement of an N-terminal arginine residue with a metallocenoyl moiety modulates the activity of WRWRW-peptides against Gram-positive and Gram-negative bacteria. MIC values of 2–6 µM for RcCO-W(RW)2 and 1–11 µM for (RW)3 were determined. Interestingly, W(RW)2-peptides derivatized with ferrocene were significantly less active than those derivatized with ruthenocene which have similar structural but different electronic properties, suggesting a major influence of the latter. The high activities observed for the RcCO-W(RW)2- and (RW)3-peptides led to an investigation of the origin of activity of these peptides using several important activity-related parameters. Firstly, killing kinetics of the RcCO-W(RW)2-peptide versus killing kinetics of the (RW)3 derivative showed faster reduction of the colony forming units for the RcCO-W(RW)2-peptide, although MIC values indicated higher activity for the (RW)3-peptide. This was confirmed by growth inhibition studies. Secondly, hemolysis studies revealed that both peptides did not lead to significant destruction of erythrocytes, even up to 500 µg/mL for (RW)3 and 250 µg/mL for RcCO-W(RW)2. In addition, toxicity against three human cancer cell lines (HepG2, HT29, MCF7) showed that the (RW)3-peptide had an IC50 value of ~140 µM and the RcW(RW)2 one of ~90 µM, indicating a potentially interesting therapeutic window. Both the killing kinetics and growth inhibition studies presented in this work point to a membrane-based mode of action for these two peptides, each having different kinetic parameters.
Keywords: antimicrobial peptides; arginine; medicinal organometallic chemistry; metallocenoyl; peptides; tryptophan